Influence of Silica Fume on the Production Process and Properties of Porous Glass Composite; Известия вузов. Химия и химическая технология; Т. 66, вып. 1 - Skirdin K. V. Kirill Vyacheslavovich (2023, 2023)
Заглавие с экрана